Bilateral short fourth metacarpal and metatarsal in a case of idiopathic primary hypoparathyroidism - Nayak, Chandrakanta; Samal, Barada Prasanna (International Journal of Advances in Medicine, 2017)
A case of bilateral symmetrical shortening of fourth metacarpal and metatarsal bones in a 25 year old female is described. She initially presented with symptoms of hypocalcaemia. Metabolic and endocrine work up concluded the underlying disorder to be idiopathic primary hypoparathyroidism contrary to the belief of psedohypoparathyroidism. The function of hand and feet were normal without any discomfort. So treatment of only hypocalcaemia was done and metacarpal, metatarsal lengthening seemed unnecessary.